Health improvement barriers among Alberta immigrants: the role of social and demographic factors (2014)
The role of social and demographic variables in influencing barriers to health improvement among Alberta immigrants and the Alberta general population was assessed in this study. Data were sourced from the Canadian Community Health Survey (CCHS) Cycle 1 of 2001. Using logistic regression analysis, it was found that job status played significant role in influencing barriers to improving immigrants’ health. Among the general Alberta population, however, immigrant status, sex and marital status played significant roles in influencing barriers to improving the health of Albertans. Reasons for immigrants not receiving care were also identified as a follow-up on the health barriers. It was suggested that, as a way of better understanding and improving the health of Albertans of all categories, those social and demographic variables that pose as barriers to health improvement should be further researched, controlled and/or eliminated. The various reasons why immigrants do not receive care should also be further investigated and addressed.